"If You've Got Friends and Neighbours": Constituency Voting Patterns for the UK Labour Party Leader in 2010. Issue 1 (2nd January 2016) - Johnston, Ron; Pattie, Charles; Pemberton, Hugh; Wickham-Jones, Mark
Abstract: Most attention in British electoral studies has been paid to the pattern of voting for parties, with relatively little to that for individual candidates. In intra-party elections, however, candidates may perform better in some areas than others, illustrating V. O. Key's well-known "friends and neighbours" effect. This paper explores whether that was so at the election for the leader of the UK Labour party in 2010, expecting each of the five candidates to perform better in their own constituency and its environs and also with those constituency parties whose MPs supported their candidature. The results are in line with the expectations, especially for one of the candidates who ran an explicitly geographical campaign.